Pola Spasial Distribusi Fasilitas Penunjang Pariwisata di Desa Jerukleueuet Kecamatan Sindangwangi Kabupaten Majalengka - Safa Arub Nadia; Sri Rum Giyarsih (Jurnal Pendidikan Geografi Undiksha, 2026)
The tourism sector plays a significant role in driving economic growth. However, tourism development in Jerukleueut Village faces several challenges, particularly in inadequate infrastructure, limited supporting tourism facilities, and uneven spatial distribution of these facilities. This study aims to identify the types of supporting tourism facilities available and to determine their spatial distribution patterns. The research utilizes the Nearest Neighbor Analysis (NNA) method to analyze the spatial distribution pattern of supporting tourism facilities. The results indicate the presence of 12 types of tourism support facilities in Jerukleueut Village, with culinary facilities being the most dominant, totaling 60 points. The findings show that the spatial distribution of these facilities tends to be clustered, as reflected by the Nearest Neighbor Ratio (NNR) value of 0.46424. These facilities are generally concentrated in strategic areas with easy access to major tourist attractions and main roads leading to those sites.